3D single-molecule tracking enables direct hybridization kinetics measurement in solution. Issue 17 (19th April 2017) - Liu, Cong; Obliosca, Judy M.; Liu, Yen-Liang; Chen, Yu-An; Jiang, Ning; Yeh, Hsin-Chih
Abstract : Spatiotemporally resolved single DNA annealing-melting kinetics measure. Abstract : Single-molecule measurements of DNA hybridization kinetics are mostly performed on a surface or inside a trap. Here we demonstrate a time-resolved, 3D single-molecule tracking (3D-SMT) method that allows us to follow a freely diffusing ssDNA molecule in solution for hundreds of milliseconds or even seconds and observe multiple annealing and melting events taking place on the same molecule. This is achieved by combining confocal-feedback 3D-SMT with time-domain fluorescence lifetime measurement, where fluorescence lifetime serves as the indicator of hybridization. With sub-diffraction-limit spatial resolution in molecular tracking and 15 ms temporal resolution in monitoring the change of reporter's lifetime, we have demonstrated a full characterization of annealing rate ( k on = 5.13 × 10 6 M −1 s −1 ), melting rate ( k off = 9.55 s −1 ), and association constant ( K a = 0.54 μM −1 ) of an 8 bp duplex model system diffusing at 4.8 μm 2 s −1 . As our method completely eliminates the photobleaching artifacts and diffusion interference, our k on and k off results well represent the real kinetics in solution. Our binding kinetics measurement can be carried out in a low signal-to-noise ratio condition (SNR ≈ 1.4) where ∼130 recorded photons are sufficient for a lifetime estimation. Using a population-level analysis, we can characterize hybridization kinetics over a wide range (0.5–125 s −1 ), even beyond the reciprocals of the lifetime monitoring temporal resolution and the average track duration.